EFEKTIVITAS PELAKSANAAN MANAJEMEN ORGANISASI KESELAMATAN DAN KESEHATAN KERJA RUMAH SAKIT (K3 RS) DI RUMAH SAKIT X SEMARANG - Kun Dwi Apriliawati; Ekawati Ekawati; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2017)
Hospital X Semarang is one of the workplaces that have a high hazard potential and employ more than 100 employees and there are visitors who should be protected such as patients, guests, and contractors. According to the Ministerial Decree N0. 1087 In 2010, each hospital must implement an occupational safety and health (OSH) of Hospital management system. The presence of organization or hospital OSH team is one of its forms. This study was intended to evaluate the implementation of the Hospital OSH organization management system. This is a qualitative study with in-depth interviews and observational approach method. Interviews were conducted to hospital OSH team member and triangulation carried out on hospital OSH chairman who responsible for the implementation of hospital OSH management system in RS X Semarang. Input indicators as resources to support the process in order to produce the expected OSH output, consists of OSH resources, tasks and authority, and budget has not been effectively implemented. Process indicators showed that hospital OSH team has conducted proper activities, but it has not been effectively implemented. The expected outcomes as an output indicators has been effectively implemented, it showed that there are documentations of each OSH activities. It can be concluded that the management implementation of OSH organization at Hospital X Semarang has not been effective. It is expected that OSH team at the hospital can improve its implementation.